Depression Augments Activity-Related Pain in Women but not in Men with Chronic Musculoskeletal Conditions - Heather Adams; Pascal Thibault; Nicole Davidson; Maureen Simmonds; Ana Velly; Michael JL Sullivan (Pain Research and Management)
OBJECTIVES: The primary objective of the present study was to examine the role of sex as a moderator of the relation between depression and activity-related pain.